2012
DOI: 10.1166/jnn.2012.4658
|View full text |Cite
|
Sign up to set email alerts
|

Study of Surface Morphology Control and Investigation of Hexagonal Indium Nitride Nanorods Grown on GaN/Sapphire Substrate

Abstract: Heteroepitaxial growth of metal-catalyst-free indium nitride (InN) nanorods on GaN/sapphire substrates by radio-frequency metal-organic molecular beam epitaxy (RF-MOMBE) system was investigated. We found that different N/In flow ratios together with the growth temperatures greatly influenced the surface morphology of InN nanorods and their structural properties. The InN nanorods have been characterized in detail using X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM). Optical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, the lattice parameters of InN film of the a- and c -axis were calculated as 3.55 and 5.71 Å, respectively. Previous literature reported that the a -axis of InN was endured and slightly strained [1]. On the contrary, our InN films had nearly relaxed on both c - and a -axis directions.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition, the lattice parameters of InN film of the a- and c -axis were calculated as 3.55 and 5.71 Å, respectively. Previous literature reported that the a -axis of InN was endured and slightly strained [1]. On the contrary, our InN films had nearly relaxed on both c - and a -axis directions.…”
Section: Resultsmentioning
confidence: 52%
“…The narrow band gap InN has been attracting considerable attention for optoelectronic and high-speed electronic devices, thanks largely to its narrow direct band gap energy of 0.7 eV, high electron mobility, and electron saturation velocity [1-4]. Recent reports have revealed promising results in the application of InN epilayers for chemical sensors [5].…”
Section: Introductionmentioning
confidence: 99%